Kemandirian Petani Dalam Mengambil Keputusan Usahatani Jagung Di Sekotong - Sabri, Ahmad Wahyu; Hayati, Hayati; Sjah, Taslim (Universitas Mataram, 2025)
The purpose of this research is to determine the level of independence of farmers in making decisions about corn farming in the Sekotong district. This paper is expected to serve as one of the references for the government in formulating policies that are more attentive to farmers' independence. This research uses a quantitative descriptive research method. The data used are primary and secondary data. The research location was determined through purposive sampling. The sampling method used was snowball sampling with a total of 30 respondents. Data analysis uses percentage index. This technique is used to describe the tendency of the respondents' independence by calculating the percentage of scores obtained through interviews with questionnaires, which are then presented in the form of a percentage distribution table. Based on the research conducted, it was found that out of 30 corn farmers in Sekotong, the majority are at self reliance in making farming decisions. There are 53% of farmers who are self reliance in the cultivation aspect, 47% self reliance in the post-harvest aspect, and 43% independent in the marketing aspect. In the aspect of fulfilling production facilities and infrastructure, there are 57% of farmers who fall into the non-independent category. This finding illustrates that some farmers in Sekotong have reached a level of self reliance.